Chemical stabilization of clay soil as road base for rural road - Kai Len, Tsai; Chee Ming, Chan; A Rahman, Noor Khazanah (Penerbit Uthm, 2018)
Rural roads form the essential access to form plantations and suburban areas. It is important for people in suburban area in connecting people towards facilities and services for life improvement. Rural road usually serve low traffic volume [1]. These roads are not meant to support traffic volume load which is too high or it could cause damage to the roads. Nonetheless, they also contribute to the country’s economic growth and development. However, the construction period and cost of the rural roads are relatively high. The conventional design consists of a multi-layer system, i.e. subgrade, sub-base, road base, binder and wearing course [2]. Long-term benefits in increasing strength and durability of the pavement subgrade by chemical stabilization can be introduce in reconstruction and new construction stages of rural roads [3]. Chemical stabilization involves injecting or blending a binder into the existing soil to improve its geotechnical properties through a chemical reaction [4]. The geotechnical properties of soil such as plasticity, unconfined compressibility strength, permeability and swelling pressure are improved by chemical stabilization. The common binder is Portland cement, lime, fly ash, chloride compound and waste materials (fiber residue, fly ash and coal) can be added to cement the soil bodies, thereby increasing the strength and stiffness [5]. The maintenance of pavement also reduced. The chemical stabilization by proprietary binder can also use in the maintenance of the existing road. It can be undertaken rapidly without the reconstruction and pre-treatment of the problematic soil by blending the existing base course materials. The chemical stabilization by proprietary binder method is a cost-effective and also as an alternative method for ground treatment. The aim of this study is to examine the range of clay soils (clay, silty clay and sandy clay) for the effective chemical stabilization with the proprietary binder. This study could be practical and applicable in road construction to help the industry in getting the effective binder dosage to be used in soil stabilization to improve the strength of the road base.